A natural history of ghosts 500 years of hunting for proof - Clarke, Roger (Penguin Books, 2013)
"Is there anybody out there?" No matter how rationally we order our lives, few of us are completely immune to the suggestion of the uncanny and the fear of the dark. What explains sightings of ghosts? Why do they fascinate us? What exactly do those who have been haunted see? What did they believe? And what proof is there? Taking us through the key hauntings that have obsessed the world, from the true events that inspired Henry James's classic The Turn of the Screw right up to the present day, Roger Clarke unfolds a story of class conflict, charlatans, and true believers. The cast list includes royalty and prime ministers, Samuel Johnson, John Wesley, Harry Houdini, and Adolf Hitler. The chapters cover everything from religious beliefs to modern developments in neuroscience, the medicine of ghosts, and the technology of ghosthunting. There are haunted WWI submarines, houses so blighted by phantoms they are demolished, a seventeenth century Ghost Hunter General, and the emergence of the Victorian flash mob, where hundreds would stand outside rumored sites all night waiting to catch sight of a dead face at a window."